Impacts of Voltage Control Methods on Distribution Circuit’s Photovoltaic (PV) Integration Limits - Anamika Dubey (Inventions, 2017)
The widespread integration of photovoltaic (PV) units may result in a number of operational issues for the utility distribution system. The advances in smart-grid technologies with better communication and control capabilities may help to mitigate these challenges. The objective of this paper is to evaluate multiple voltage control methods and compare their effectiveness in mitigating the impacts of high levels of PV penetrations on distribution system voltages. A Monte Carlo based stochastic analysis framework is used to evaluate the impacts of PV integration, with and without voltage control. Both snapshot power flow and time-series analysis are conducted for the feeder with varying levels of PV penetrations. The methods are compared for their impacts on (1) the feeder’s PV hosting capacity; (2) the number of voltage violations and the magnitude of the largest bus voltage; (3) the net reactive power demand from the substation; and (4) the number of switching operations of feeder’s legacy voltage support devices i.e., capacitor banks and load tap changers (LTCs). The simulation results show that voltage control help in mitigating overvoltage concerns and increasing the feeder’s hosting capacity. Although, the legacy control solves the voltage concerns for primary feeders, a smart inverter control is required to mitigate both primary and secondary feeder voltage regulation issues. The smart inverter control, however, increases the feeder’s reactive power demand and the number of LTC and capacitor switching operations. For the 34.5-kV test circuit, it is observed that the reactive power demand increases from 0 to 6.8 MVAR on enabling Volt-VAR control for PV inverters. The total number of capacitor and LTC operations over a 1-year period also increases from 455 operations to 1991 operations with Volt-VAR control mode. It is also demonstrated that by simply changing the control mode of capacitor banks, a significant reduction in the unnecessary switching operations for the capacitor banks is observed.